More than a game [videorecording (DVD)] - Belman, Kristopher; James, LeBron; Cotton, Sian; McGee, Willie; Travis, Romeo; Joyce, Dru, III; Joyce, Dru, II (Lionsgate, 2009)
Follows Akron's St. Vincent-St. Mary Fighting Irish high school basketball team (featuring five future NBA players, including superstar LeBron James) as they win their way to national acclaim.